2020
DOI: 10.1634/theoncologist.2019-0426
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Financial Needs Following Diagnosis of Breast Cancer in a Setting with Universal Health Coverage

Abstract: Background A diagnosis of cancer negatively impacts the financial wellbeing of affected individuals as well as their households. We aimed to gain an in‐depth understanding of the financial needs following diagnosis of breast cancer in a middle‐income setting with universal health coverage. Materials and Methods Twelve focus group discussions (n = 64) were conducted with women with breast cancer from two public and three private hospitals. This study specifically focused on (a) health costs, (b) nonhealth costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…Country-specific analyses revealed similar findings [ 16 – 18 ]. Our recent qualitative inquiry in a multiethnic population of Malaysian women with breast cancer had also revealed that unmet financial needs related to cancer treatment and healthcare might exist even among patients from high-income groups, as well as those with health insurance [ 19 ]. These needs range from financial assistance to cover out-of-pocket payments for medical and non-medical costs following cancer diagnosis, to navigation through the complex system to claim medical insurance or social security benefits, and return to work assistance.…”
Section: Economic Impact Of Cancer and Covid-19 In Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Country-specific analyses revealed similar findings [ 16 – 18 ]. Our recent qualitative inquiry in a multiethnic population of Malaysian women with breast cancer had also revealed that unmet financial needs related to cancer treatment and healthcare might exist even among patients from high-income groups, as well as those with health insurance [ 19 ]. These needs range from financial assistance to cover out-of-pocket payments for medical and non-medical costs following cancer diagnosis, to navigation through the complex system to claim medical insurance or social security benefits, and return to work assistance.…”
Section: Economic Impact Of Cancer and Covid-19 In Southeast Asiamentioning
confidence: 99%
“…Many cancer patients also face numerous issues while working following a diagnosis with cancer. We recently found that among Malaysian breast cancer survivors, besides experiencing catastrophic loss of household income, many recounted facing discriminations at the workplace due to their cancer [ 19 ], such as being forced to resign. It is not unthinkable that the pandemic may only have worsened the existing workplace discrimination when employers are forced to weigh in the organizational goals against the individual sufferings of employees with cancer.…”
Section: Economic Impact Of Cancer and Covid-19 In Southeast Asiamentioning
confidence: 99%
“…The introduction of newer diagnostic, pharmacological, and treatment technologies coupled with the long-term care of cancer patients contributes towards a rapid escalation of cost [ 3 , 11 ]. On top of these, Malaysia’s public healthcare system also incorporates additional subsidies for the population above the age of 60 years, which forms most of the oral cancer incidences [ 12 ]. Consequently, the bulk of treatment costs will be borne by the Ministry of Health with minimal reimbursement from fee-for-service [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the bulk of treatment costs will be borne by the Ministry of Health with minimal reimbursement from fee-for-service [ 7 ]. The recent implementation of the PeKa B40 scheme, which provides financial incentives for transport and the completion of cancer treatment further adds to this existing financial burden [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The management of new cancer cases alone could amount to RM108 million (USD 26 million) per year excluding the costs for therapies, surveillance, and palliative care (2). Besides, patients may also experience loss of employment and earnings following the diagnosis of cancer (3). Surgery is the best hope of cure (2) and remains the preferred modality of treatment for cancer (4).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%